Enhancing Indonesian vocational high school graduate’s competence in the world of work after covid-19 pandemic through innovative learning models - Putra, Ismada Firdaus Mandala (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research explores innovative learning models to ensure that Indonesian vocational high school graduates still have an excellent competency after being hit by the Covid-19 pandemic. This research adopted the qualitative method by conducting content analysis. Based on the analysis, this study has discovered three innovative learning methods, namely [1] researchbased learning; to enhance data literacy, [2] interactive multimedia-based learning; for increasing technological literacy, and [3] project-based learning; conducted to empower human literacy. The students’ capabilities to compete in the corporate world are better if they apply these three learning models. It would also reduce the risk of unemployment due to technological disruption during the pandemic and the increased population by acquiring these literacy skills. It is hoped that vocational high school graduates will be hired fast and able to take part in the corporate world and have the three new literacy skills as the principal capital in taking part in the corporate world.